Banking Digitalization through Self-Service Technology toward Customer Behavior at Bank Syariah Indonesia (BSI) Yogyakarta City - Imran, Ahmad Fadhil; Bado, Basri; Solikhatun, Ismi (Jurnal Ilmiah Ekonomi Islam, 2023)
Banking sector digitization has gained significant attention towards addressing the challenges of an advancing era. Self-Service Technology, as a form of digitalization, empowers public access to banking services is an aspect that needs to be explored. This research employs a quantitative approach with a descriptive method. The population of this study are all customers registered in Bank Syariah Indonesia (BSI) in the city of Yogyakarta. Purposive Sampling is used as a sampling technique. There are 141 BSI users in Yogyakarta who use BSI. The results indicate that there is a positive influence of ATM on Customer Behavior, a positive influence of Mobile Banking on Customer Behavior, and a negative influence of Internet Banking on Customer Behavior. The research also demonstrates that the impact of Self-Service Technology (SST), as observed through the variables of ATM, Mobile Banking, and Internet Banking, collectively affects the variable of Customer Behavior. These findings suggest that the banking digitalization through self-service technology indeed influences customer behavior in decision-making at Bank Syariah Indonesia (BSI) in Yogyakarta. The extent of self-service technology offered has a proportional impact on customer behavior.